Optical fiber sensing implant structure and packaging method thereof, battery and electric vehicle
Patent Information
- Application Number
- CN202611105474.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本发明提供一种光纤传感植入结构及其封装方法、电池和电动汽车,解决现有电池传感器封装技术中温度-应变交叉敏感和密封易失效的问题
通过设置应力解耦导管,并将光纤传感器悬浮于导管中心空腔,使其在管内处于无约束悬浮状态,利用力学隔离机制实现温-压解耦,并彻底隔绝了电池壳体变形、卷芯膨胀或振动等外部机械应力对光纤传感器的直接传递;同时,导管下端与正极防爆盖板保持安全间距,避免接触引发的应力干扰,由此获得的测量信号仅来源于温度、压力或应变等真实物理量,显著提升了传感精度与可靠性;采用分级密封组件突破了微米级缝隙的深层灌注难题:第一层利用厌氧胶在环形微缝中经毛细渗透并固化,形成致密填充层;第二层采用光固化树脂在端口外形成半球状包裹,前者微观堵漏抗腐蚀+后者宏观抗振防断裂的双重密封协同作用,即使电池长期循环或处于高气压、电解液浸润环境下,仍能有效防止电解液泄漏及外部水分侵入;克服了现有原位光纤传感中交叉敏感和密封易失效的问题,具有高精度和高可靠性。
Smart Images

Figure CN123018206A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery safety monitoring and sensing packaging technology, and in particular to an optical fiber sensing implantation structure and its packaging method, as well as batteries and electric vehicles. Background Technology
[0002] Because cylindrical lithium-ion batteries consist of positive and negative electrodes and a separator wound together to form a core structure, the core has high radial thermal resistance. This results in a 15°C-30°C thermal hysteresis between the core area and the outer casing, making it impossible for traditional casing-mounted temperature sensors to capture the true temperature of the battery cell. Currently, the industry commonly uses fiber Bragg grating (FBG) sensors embedded inside the battery for in-situ temperature measurement. However, existing embedding methods have two major drawbacks: First, directly sealing the optical fiber within the core cavity with adhesive causes stress from core expansion to be transmitted to the fiber through the adhesive, leading to FBG wavelength drift affected by both temperature and strain, resulting in severe signal cross-coupling and temperature measurement errors exceeding ±10°C. Second, single-stage adhesive sealing is prone to micro-cracks under long-term electrolyte corrosion and thermal alternation, leading to electrolyte leakage or external moisture infiltration, causing corrosion and battery failure.
[0003] Therefore, how to solve the problems of temperature-strain cross-sensitivity and easy seal failure in existing battery sensor packaging technology has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0004] This invention provides an optical fiber sensing implantation structure and its packaging method, as well as a battery and an electric vehicle, solving the problems of temperature-strain cross-sensitivity and easy seal failure in existing battery sensor packaging technologies.
[0005] To address the aforementioned technical problems, the first aspect of this invention provides an optical fiber sensing implantation structure, comprising a stress decoupling catheter and a graded sealing assembly; wherein, The stress decoupling conduit has an axially penetrating central cavity, allowing the fiber optic sensor to pass through the central cavity and a preset gap to be provided between it and the inner wall of the stress decoupling conduit; the outer diameter of the central cavity is smaller than the diameter of the mounting hole opened at the center of the negative end face of the battery body, so as to form an annular micro-slit between the outer wall of the stress decoupling conduit and the inner wall of the mounting hole; the lower end of the stress decoupling conduit extends into the battery core cavity in a suspended manner, and a safe distance is provided between the bottom end and the inner side of the positive electrode explosion-proof cover plate of the battery body; The graded sealing assembly is disposed at the assembly interface between the mounting hole and the stress decoupling conduit; the graded sealing assembly includes a first sealing layer and a second sealing layer arranged coaxially; wherein, the first sealing layer is formed by capillary penetration and curing of anaerobic adhesive in the annular micro-slit, filling the annular micro-slit; the second sealing layer is formed by curing with photocurable resin, covering the external port of the mounting hole and the surface of the battery casing, and hemispherically wrapping the exposed section of the stress decoupling conduit and the outer side of the lead-out section of the fiber optic sensor.
[0006] As one preferred embodiment, the stress decoupling conduit is made of polyetheretherketone (PEEK) and has a Young's modulus of 3.6 GPa-4.0 GPa.
[0007] As one preferred embodiment, the stress decoupling conduit has a length of 68 mm, an outer diameter of 0.7 mm, and an inner diameter of 0.4 mm.
[0008] As one preferred embodiment, the aperture is 0.02mm-0.05mm larger than the outer diameter; the width of one side of the annular microslit is 25μm.
[0009] As one preferred embodiment, the preset gap is 122μm-125μm; the safety distance is 1.5mm-2.5mm.
[0010] As one preferred embodiment, the anaerobic adhesive is made of methacrylate and has a dynamic viscosity of 200 mPa·s-500 mPa·s.
[0011] As one preferred embodiment, the photocurable resin is made of acrylate and has a Shore hardness of not less than D70 after curing; the bottom diameter of the hemisphere is 3mm-4mm and the height of the hemisphere is 2mm-3mm.
[0012] A second aspect of the present invention provides a method for encapsulating an optical fiber sensing implanted structure as described in the first aspect, comprising: Under an inert gas protective environment, a mounting hole is drilled at the central axis of the negative terminal face of the battery body so that the mounting hole penetrates the battery casing and enters the core cavity; the diameter of the mounting hole is larger than the outer diameter of the central cavity that runs through the stress decoupling conduit axially. The stress decoupling conduit is vertically inserted into the mounting hole so that the bottom end of the stress decoupling conduit is suspended in the core cavity, and an annular micro-slit is formed between the stress decoupling conduit and the mounting hole. The fiber optic sensor is inserted into the stress decoupling conduit through the central cavity, so that a preset gap is provided between the outer surface of the fiber optic sensor and the inner wall of the stress decoupling conduit. Anaerobic adhesive is applied to the root of the connection between the mounting hole and the stress decoupling conduit. The anaerobic adhesive is then allowed to penetrate deep into the annular micro-slit using capillary action and naturally cures in an anaerobic environment to form a primary permeation sealing structure. A photocurable resin is coated on the outer side of the external port of the mounting hole and the exposed section of the stress decoupling conduit, and the photocurable resin is cured by irradiation with ultraviolet light of a specific wavelength to form a hemispherical encapsulated secondary reinforcement structure.
[0013] A third aspect of the present invention provides a battery comprising the fiber optic sensing implantation structure as described in the first aspect.
[0014] A fourth aspect of the present invention provides an electric vehicle comprising a battery as described in the third aspect.
[0015] Compared with the prior art, the beneficial effects of the embodiments of the present invention are as follows: By setting up a stress decoupling conduit and suspending the fiber optic sensor in the central cavity of the conduit, it is placed in an unconstrained suspended state within the conduit. This utilizes a mechanical isolation mechanism to achieve temperature-pressure decoupling and completely isolates the direct transmission of external mechanical stress, such as battery casing deformation, core expansion, or vibration, to the fiber optic sensor. Simultaneously, a safe distance is maintained between the lower end of the conduit and the positive electrode explosion-proof cover to avoid stress interference caused by contact. The measurement signals obtained are derived only from real physical quantities such as temperature, pressure, or strain, significantly improving sensing accuracy and reliability. A graded sealing component overcomes the challenge of deep filling in micron-level gaps: the first layer uses anaerobic adhesive to form a dense filling layer through capillary penetration and curing in the annular micro-slit; the second layer uses photocurable resin to form a hemispherical wrap around the port. The synergistic effect of the former's microscopic leak-stopping and corrosion resistance combined with the latter's macroscopic vibration resistance and fracture prevention effectively prevents electrolyte leakage and external moisture intrusion, even during long-term battery cycling or in high-pressure or electrolyte-immersed environments. This overcomes the problems of cross-sensitivity and easy seal failure in existing in-situ fiber optic sensors, resulting in high accuracy and high reliability. Attached Figure Description
[0016] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a front sectional view of the overall axial longitudinal section of the fiber optic sensing implantation structure provided in a certain embodiment of the present invention; Figure 2This is a partially enlarged cross-sectional view of a graded sealing assembly provided in a certain embodiment of the present invention; wherein, region A is the junction of the mounting hole and the stress decoupling conduit; Figure 3 This is a schematic diagram of the microscopic stress distribution analysis principle provided in a certain embodiment of the present invention; Figure 4 This is a schematic diagram of the microscopic evolution process of deep capillary permeation provided in a certain embodiment of the present invention; Figure 5 This is a flowchart of a packaging method for an optical fiber sensing implantation structure provided in a certain embodiment of the present invention; Figure 6 This is a diagram showing the evolution of the state of a packaging process node according to a certain embodiment of the present invention; Figure 7 This is a comparison curve data diagram of the center wavelength drift trajectory of FBG optical fiber under the same 1C constant current charge and discharge cycle conditions for different structures provided in a certain embodiment of the present invention; Figure 8 This is a radar image showing the attenuation of vacuum leak rate in high-precision helium mass spectrometry leak detection before and after 100 extreme temperature shocks for different packaging systems provided in a certain embodiment of the present invention. Figure label: Among them, 10 is the battery body; 11 is the mounting hole; 12 is the core cavity; 13 is the battery electrode roll; 14 is the positive electrode explosion-proof cover; 20 is the stress decoupling conduit; 21 is the central cavity; 22 is the preset gap; 30 is the fiber optic sensor; 31 is the FBG sensing grid section; 40 is the graded sealing assembly; 41 is the first sealing layer; and 42 is the second sealing layer. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings and examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] It should be understood that the step numbers used in the text are for ease of description only and are not intended to limit the order in which the steps are performed.
[0020] It should be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.
[0021] The terms “comprising” and “including” indicate the presence of the described feature, whole, step, operation, element and / or component, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0022] The term “and / or” refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes these combinations.
[0023] The drive motor system and power battery system are crucial technologies for electric vehicles, and their performance and safety directly determine the vehicle's dynamics and market viability. Lithium-ion batteries, due to their advantages such as high energy density, low self-discharge rate, and no memory effect, dominate in electric vehicles (EVs) and large-scale electrochemical energy storage power stations. However, high energy density inevitably brings serious safety hazards. Under extreme abuse conditions such as overcharging, over-discharging, high temperature, and internal micro-short circuits, lithium-ion batteries are highly susceptible to inducing a chain of exothermic reactions (such as decomposition of the solid electrolyte interphase (SEI) film, oxygen release from the cathode material, and high-temperature combustion of the electrolyte), ultimately leading to catastrophic thermal runaway (TR).
[0024] The internal structure of a cylindrical battery consists of a jelly roll formed by tightly winding a positive electrode, a porous separator, and a negative electrode. Due to the presence of multi-layer solid-liquid interface thermal resistance, the jelly roll has an extremely high radial thermal resistance coefficient. During high-rate charge and discharge (such as extreme charging conditions above 4C) or in the early stages of thermal runaway, heat in the battery's mandrel cannot be rapidly conducted to the outer casing, causing a rapid rise in core temperature while the outer casing surface temperature changes slowly. Studies have shown that the radial temperature difference (thermal hysteresis) between the two can be as high as 15°C to 30°C. Therefore, traditional temperature monitoring solutions based on attaching NTC thermistors or PT100 to the battery casing surface completely lose their ability to accurately predict the early internal thermal state when facing next-generation high-voltage fast charging scenarios.
[0025] To accurately capture the true internal thermodynamics and strain characteristics, in recent years, the academic community has proposed an in-situ testing technique that involves drilling holes in the metal bottom shell of a battery and directly implanting fiber Bragg grating (FBG) sensors into the central cavity of the core. Compared with traditional thermocouples, FBG fiber sensors have unique advantages such as resistance to strong electromagnetic interference, extremely small size (the diameter of the bare fiber is only 125μm, which is convenient for minimally invasive implantation), high-voltage isolation resistance, and multi-point multiplexing of a single fiber.
[0026] However, current implantation and encapsulation technologies face two drawbacks known as "industry barriers" in their ability to stably embed high-precision optical sensors in the extreme electrochemical and mechanical environments of batteries over long periods: Defect 1: Severe temperature-pressure cross-sensitivity leads to serious distortion of the temperature measurement signal. During the large-scale charge-discharge cycle, the periodic insertion and extraction of lithium ions (Li+) between the graphite anode layers leads to an increase in the interlayer spacing of the graphite lattice, causing significant volume expansion of the entire electrode core (the so-called "battery breathing effect"). Current packaging processes typically involve simply inserting an optical fiber through a central hole and then directly injecting a large amount of epoxy resin to solidify it into a rigid whole with the electrode and steel casing. This results in enormous radial compressive stress generated by the electrode expansion, which is directly and unbufferedly transmitted and coupled to the precision fiber optic grating (FBG) region through the rigid epoxy colloid. Since the center wavelength of the FBG is sensitive to both strain and temperature, the wavelength drift signal received by the demodulator is a nonlinear superposition of temperature abrupt changes and stress compression. This causes the measured temperature curve to exhibit a drastic "saddle-shaped" abrupt change and a "pseudo-temperature rise" peak at the end of charging, with measurement errors often exceeding ±10℃, completely negating its value as a high-precision scientific research benchmark sensor.
[0027] Defect 2: Long-term failure of airtightness (chronic leakage) caused by strong electrolyte penetration corrosion and thermal alternation. The main salt in lithium-ion battery electrolytes is mostly lithium hexafluorophosphate (LiPF6), and its solvent system includes ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), exhibiting extremely high volatility, permeability, and organic solubility. Traditional single-component or two-component adhesives (such as conventional epoxy adhesives, silicone, and acrylic structural adhesives) undergo severe swelling, softening, and degradation of their long molecular chains under prolonged immersion in the electrolyte. Even more critically, the coefficient of thermal expansion (CTE) of the high-hardness cured adhesive differs significantly from that of the battery casing (nickel-plated steel or aluminum alloy) (steel has a CTE of approximately 12 ppm / ℃, while epoxy resin often has a CTE greater than 60 ppm / ℃). Under the high and low temperature cycling (e.g., -40℃ to 85℃) thermal shock of actual vehicle operation, the interface is highly susceptible to micron-level fatigue cleavage cracks. These cracks form capillary channels for electrolyte vaporization and leakage; at the same time, trace amounts of moisture in the outside air seep into the battery through the cracks and react with LiPF6 to generate highly corrosive hydrofluoric acid (HF), which will not only instantly corrode the glass optical fiber made of silicon dioxide (SiO2), but also cause gas to be generated inside the battery, bulge, and eventually become unusable.
[0028] To overcome the problems of "stress cross-coupling distortion" and "single-stage adhesive seal corrosion failure" encountered in existing technologies for in-situ fiber optic implantation sensing in batteries, the first aspect of this invention provides a fiber optic sensing implantation structure adapted to cylindrical lithium-ion batteries such as 18650, 21700, and 4680. This structure not only achieves absolutely pure internal single-temperature signal extraction from a mechanical perspective but also achieves long-term leak-proof stability through a composite chemical infiltration and coagulation technology. The structure includes a stress decoupling conduit 20 and a graded sealing assembly 40; wherein, The stress decoupling conduit 20 has an axially penetrating central cavity 21, allowing the fiber optic sensor 30 to pass through the central cavity 21 and a preset gap 22 between it and the inner wall of the stress decoupling conduit 20; the outer diameter of the central cavity 21 is smaller than the diameter of the mounting hole 11 opened at the center of the negative end face of the battery body 10, so as to form an annular micro-slit between the outer wall of the stress decoupling conduit 20 and the inner wall of the mounting hole 11; the lower end of the stress decoupling conduit 20 extends into the battery core cavity 12 in a suspended manner, and a safe distance is provided between the bottom end and the inner side of the positive electrode explosion-proof cover plate 14 of the battery body 10; The graded sealing assembly 40 is disposed at the assembly interface between the mounting hole 11 and the stress decoupling conduit 20; the graded sealing assembly 40 includes a first sealing layer 41 and a second sealing layer 42 arranged coaxially; wherein, the first sealing layer 41 is formed by capillary penetration and curing of anaerobic adhesive in the annular micro-slit, filling the annular micro-slit; the second sealing layer 42 is formed by curing with photocurable resin, covering the external port of the mounting hole 11 and the surface of the battery casing, and wrapping the exposed section of the stress decoupling conduit 20 and the lead-out section of the fiber optic sensor 30 in a hemispherical shape.
[0029] The overall axial longitudinal section front view of the fiber optic sensing implanted structure is shown below. Figure 1 As shown, Figure 1 A partially enlarged cross-sectional view of the graded sealing assembly 40 in region A (i.e., the junction of mounting hole 11 and conduit) is shown below. Figure 2 As shown. Please refer to [the original text]. Figure 1 and Figure 2 The fiber optic sensing implantation structure includes a stress decoupling conduit 20 and a graded sealing assembly 40. The stress decoupling conduit 20 allows the fiber optic sensor 30 to suspend in its central cavity 21, physically cutting off the stress transmission path and enabling pure temperature signal acquisition. The graded sealing assembly 40 adopts a two-stage sealing structure of "anaerobic adhesive deep penetration + photocurable resin external reinforcement" to solve the problems of electrolyte penetration and temperature fatigue cracking, and achieve airtight barrier to the electrolyte.
[0030] The stress decoupling conduit 20 (referred to as the conduit) is a hollow straight tube with a length of 68 mm, an outer diameter of 0.7 mm, and an inner diameter of 0.4 mm. It is made of engineering plastic (preferably polyetheretherketone PEEK) with high elastic modulus and resistance to electrolyte corrosion, exhibiting a Young's modulus of 3.6 GPa-4.0 GPa, strong chemical inertness, resistance to electrolyte corrosion, and high rigidity. The stress decoupling conduit 20 is an independent load-bearing component, used to independently bear the radial compressive stress generated by the expansion of the battery electrode roll 13 (multi-layer wound structure).
[0031] The stress decoupling conduit 20 is integrally inserted and fixed inside the mounting hole 11 at the center of the negative terminal face of the battery body 10. The upper end of the conduit extends to the outside of the negative terminal face of the battery body 10 to form an exposed section (also called the lead-out end), and the lower end of the conduit extends into the core cavity 12 (also called the core center cavity 21) of the battery. A safety distance is reserved between the bottom end of the conduit and the inner side of the positive electrode explosion-proof cover 14 of the battery body 10, so as not to contact any internal components. The safety distance is 1.5mm-2.5mm, preferably 2mm, to prevent the positive electrode from being punctured by bumps and causing a short circuit. The depth of the mounting hole 11 is preferably 3.0mm, which penetrates the nickel-plated steel shell of the battery and the internal insulation components, and directly connects to the core cavity 12.
[0032] The stress decoupling conduit 20 has an axially penetrating central cavity 21, which serves as the mounting space for the fiber optic sensor 30. The fiber optic sensor 30 is a fiber Bragg grating (FBG) sensor with a polyimide anti-corrosion coating, with a bare fiber diameter of 125 μm. It is integrally mounted within the central cavity 21 of the stress decoupling conduit 20, with a predetermined gap 22 between its outer surface and the inner wall of the conduit 20. This predetermined gap 22 is 122 μm-125 μm, preferably 122.5 mm. The predetermined gap 22 ensures complete non-contact between the two, allowing the fiber optic sensing component to suspend within the conduit cavity without any rigid contact with the inner wall, achieving complete isolation from mechanical stress. Thus, the minute deformation of the conduit caused by the expansion of the core cannot contact the internally suspended fiber, completely blocking the transmission of mechanical stress to the fiber at a physical level and eliminating strain interference with the temperature measurement signal.
[0033] The fiber optic sensor 30 has an FBG sensing grid section 31 in its middle, with a length of 3mm. This section precisely corresponds to the axial geometric center of the battery core (the extreme region of the cell's thermal core). The depth of the grid section from the upper end of the stress decoupling conduit 20 is preferably 32.5mm. The upper end of the fiber optic sensor 30 extends outward from the outlet of the stress decoupling conduit 20 for connecting to an external signal demodulation device. The entire fiber optic sensor 30 is used to acquire pure temperature signals inside the battery, eliminating signal distortion caused by strain.
[0034] The outer diameter of the central cavity 21 is smaller than the diameter of the mounting hole 11 on the battery casing, thereby forming a uniformly wide annular microslit between the outer wall of the stress decoupling conduit 20 and the inner wall of the mounting hole 11, which provides the physical conditions for subsequent capillary sealing. The width of one side of the annular microslit is 25 μm; the diameter of the mounting hole 11 is 0.02 mm to 0.05 mm larger than the outer diameter of the central cavity 21.
[0035] The graded sealing assembly 40 is located at the assembly interface between the mounting hole 11 and the stress decoupling conduit 20. It consists of a first sealing layer 41 and a second sealing layer 42 arranged coaxially, forming a dual protection system of "microscopic seepage prevention + macroscopic reinforcement".
[0036] The first sealing layer 41 fills the annular micro-gap between the outer wall of the stress decoupling conduit 20 and the metal hole wall of the mounting hole 11. The anaerobic adhesive penetrates the entire gap via capillary action, and after curing, forms a dense polymer cross-linked body, which can also be understood as a permeable airtight layer. This airtight layer completely fills the annular micro-gap, tightly adhering to the metal hole wall and the outer wall of the conduit, blocking the penetration and diffusion channels of electrolyte and water vapor, achieving deep airtightness and corrosion protection. The anaerobic adhesive is made of methacrylate, with a dynamic viscosity of 200 mPa·s-500 mPa·s.
[0037] The second sealing layer 42 is formed on the external port of the mounting hole 11 on the negative terminal side of the battery body 10 and on the surface of the battery casing. It has a hemispherical colloidal structure with a bottom diameter of 3mm-4mm (preferably 3.5mm) and a height of 2mm-3mm (preferably 2.5mm). It completely covers the exposed section of the stress decoupling conduit 20 and the outer side of the lead-out section of the fiber optic sensor 30. It is formed by UV-curing resin and possesses high mechanical strength, used to improve the overall structure's resistance to pull-out, vibration, and high / low temperature thermal cycling. The UV-curing resin is made of acrylate, and its Shore hardness after curing is not less than D70.
[0038] Working principle of fiber optic sensing implanted structure: In traditional potting encapsulation, the strong radial compressive stress generated by the lithium insertion and expansion of the battery electrode is directly applied to the optical fiber through the adhesive. In this invention, the high-rigidity PEEK conduit is considered as an isotropic thick-walled cylinder subjected to uniform external pressure. According to Lamé's analytical solution in elasticity, under the action of an internal and external pressure difference, the radial stress at any radius r of the conduit... With circumferential stress for: In the formula, External pressure; r o The outer diameter of the catheter;r i This refers to the inner diameter of the catheter.
[0039] According to the generalized Hooke's law, the inner wall of the PEEK catheter ( r = r i The radial contraction displacement μ at the location is r i This can be deduced as: In the formula, It features a high Young's modulus (up to 3.6 GPa-4.0 GPa) in PEEK material.
[0040] The principle diagram of microscopic stress distribution analysis is shown below. Figure 3 As shown, the inference proves that: the extreme pressure value under extreme expansion conditions... =8MPa, and catheter size ( r o =0.7mm, r i Substituting (=0.4mm) into the above formula, the maximum centripetal displacement of the inner wall of the conduit is calculated to be only about 1.5um. In this invention, a free gap is reserved between the outer diameter of the optical fiber and the inner diameter of the tube. Compared with the outer diameter, no matter how violently the battery expands, the inner wall of the conduit can never reach and squeeze the internally suspended optical fiber, and the stress transmission path is cut off from the physical space.
[0041] The central reflection wavelength of a bare FBG grating exposed to complex environments shifts. Subject to axial strain The dual coupling control with temperature change ΔT, its photoelastic and thermo-optical effect coupling equation is: In the formula, The reflected wavelength; The effective elastic-optical coefficient of the optical fiber core (0.22 is commonly used for quartz glass). The thermal expansion coefficient of optical fiber (approximately) ); Thermo-optic coefficient (approximately) ).
[0042] This invention reduces the dimension of the mechanical strain experienced by optical fibers: The original extremely complex nonlinear two-parameter coupled equation is instantly reduced in dimension to an extremely pure one-dimensional linear mapping equation of temperature: In the formula, The temperature sensitivity constant (usually approximately) (In the 1550nm band). This decoupling equation provides a clean and reliable raw physical signal base for the demodulator's software post-processing. Traditional high-viscosity epoxy adhesives cannot solve microscopic gaps ( This invention innovatively utilizes physical surface tension to illustrate the microscopic evolution process of deep infiltration through capillary gaps in deep perfusion. (See diagram below.) Figure 4 As shown, its penetration depth Over time The evolutionary pattern follows the Washburn dynamics equations: In the formula, The surface tension of the anaerobic liquid phase. The dynamic contact angle between the adhesive and the drilled steel shell wall. The dynamic viscosity of the adhesive is denoted as . The equivalent hydraulic radius of the annular gap.
[0043] This invention achieves its goal by precisely selecting products with ultra-low viscosity and high wettability (minimal viscosity). The methacrylate anaerobic gel (corner) is driven by both gravity and capillary attraction, causing it to swell in a very short time. Within, penetration depth It can achieve penetration The metal cap thickness is at its maximum value. Subsequently, under the catalysis of metal ions, it solidifies from the bottom up from the deep layer, thereby achieving 100% dense deep crack sealing.
[0044] During the charging and discharging of lithium-ion batteries (especially high-rate lithium insertion / extraction) and thermal runaway expansion, the core generates complex radial and tangential alternating stresses reaching several megapascals (MPa). The special PEEK (polyether ether ketone) conduit introduced in this invention possesses extremely high tensile modulus and yield strength. According to solid mechanics models, the PEEK tube wall acts as a rigid support skeleton, completely absorbing and resisting surrounding mechanical compression; simultaneously, the pre-set gap 22 on one side within the tube creates a "zero-stress microenvironment," allowing the optical fiber to be in a "freely suspended" state. Therefore, the center wavelength drift of the fiber Bragg grating (FBG) is only temperature-dependent, eliminating the "temperature-strain cross-sensitivity" interference caused by direct contact between the fiber and the electrode in traditional optical fibers from a physical source, and abandoning the dual-fiber differential compensation algorithm which easily generates cumulative errors.
[0045] The carbonate electrolytes (such as DMC / DEC) inside the battery have extremely low surface tension, resulting in strong penetration and corrosive properties. This invention cleverly utilizes a 25μm micron-scale annular microslit formed by the precise assembly between the drilled hole and the conduit. According to the Young-Laplace equation, this microscale gap can generate extremely strong capillary attraction. In the first stage of curing, the low-viscosity anaerobic adhesive spontaneously and deeply fills all the micropores between the rough metal pore walls and the PEEK tube under the drive of capillary force, and undergoes free radical polymerization under the anaerobic and metal ion catalysis to form the first dense polymer cross-linked locking layer; the subsequent second stage of high-strength UV / epoxy curing provides a macroscopic tensile-resistant physical armor on the outside. This dual-tiered defense of "internal microscopic penetration + external macroscopic enhancement" completely cuts off the Knudsendiffusion channels of the electrolyte.
[0046] The optical fiber is suspended in the air gap. Air has low static thermal conductivity, but due to the extremely small space (micrometer level) inside the encapsulated microtube, when the temperature of the "heat core" inside the battery fluctuates drastically, the microenvironment inside the tube can quickly establish thermal equilibrium through microscale thermal convection and thermal radiation. Its extremely small thermal capacity ensures that the lag time of temperature sensing is compressed to the millisecond level, realizing high-fidelity capture of transient characteristic signals in the early stage of thermal runaway.
[0047] This invention, through an "in-pipe suspension" strategy, achieves a significant leap in temperature measurement accuracy and stability compared to traditional direct burial methods. Single-layer adhesives struggle to simultaneously achieve both "high flowability and deep penetration" and "high modulus and tensile strength." This invention combines "anaerobic adhesive penetration and anchoring of the substrate" with "UV resin spot sealing," the former providing microscopic leak sealing and corrosion resistance, and the latter macroscopic vibration resistance and fracture prevention. Rigorous high-pressure helium mass spectrometry leak testing shows that the vacuum leak rate of this structure is lower than... This ensures "zero leakage" after thousands of thermal cycles.
[0048] In another embodiment, such as Figure 5 As shown, a second aspect of the present invention provides a packaging method for an optical fiber sensing implanted structure as described in the first aspect, comprising: S1. Under an inert gas protective environment, a mounting hole is drilled at the central axis of the negative terminal face of the battery body so that the mounting hole penetrates the battery casing and enters the core cavity; the diameter of the mounting hole is larger than the outer diameter of the central cavity that runs through the stress decoupling conduit axially. S2. Insert the stress decoupling conduit vertically into the mounting hole so that the bottom end of the stress decoupling conduit is suspended in the core cavity, and form an annular micro-slit between the stress decoupling conduit and the mounting hole. S3. Insert the fiber optic sensor through the central cavity into the stress decoupling conduit so that a preset gap is provided between the outer surface of the fiber optic sensor and the inner wall of the stress decoupling conduit. S4. Apply anaerobic adhesive to the root of the connection between the mounting hole and the stress decoupling conduit, and use capillary action to allow the anaerobic adhesive to penetrate deep into the annular micro-slit, and cure naturally in an anaerobic environment to form a primary permeation sealing structure. S5. Apply a light-curing resin to the outer side of the external port of the mounting hole and the exposed section of the stress decoupling conduit, and use ultraviolet light of a specific wavelength to cure the light-curing resin to form a hemispherical encapsulated secondary reinforcement structure.
[0049] Specifically, based on the fiber optic sensing implantation structure provided in the first aspect, this invention also provides a packaging method for the fiber optic sensing implantation structure, comprising: multi-level minimally invasive perforation in an inert environment, decoupling catheter implantation and tolerance control, sensor suspension calibration, a first-stage micro-slit capillary infiltration process, and a second-stage UV spot shaping process; wherein... Multi-stage minimally invasive drilling in an inert environment: First, the battery body to be processed is discharged at a constant current to a cutoff voltage of 2.5V to reduce the internal activity of the battery and prevent electrolyte oxidation and fire during drilling. The battery is then moved into a sealed glove box, where high-purity argon gas is continuously introduced to create an inert environment, controlling the oxygen and moisture content inside the box to be below 0.1ppm. Using a miniature high-precision CNC machine tool with a tungsten carbide micro drill bit, the battery body is fixed with the negative terminal facing upwards, and the mounting hole is drilled in a low-speed, low-feed mode: the spindle speed is controlled at 500rpm-700rpm, the axial feed rate is 0.04mm / s-0.06mm / s, and the drilling depth is 2.8mm-3.2mm. During the drilling process, a negative pressure suction nozzle is set next to the drill bit to remove steel chips and insulating debris in real time, preventing debris from falling into the core cavity and causing internal micro-short circuits. After drilling is completed, remove the drill bit, leaving the complete mounting hole so that it penetrates the battery casing and enters the core cavity. The diameter of the mounting hole is larger than the outer diameter of the central cavity that runs axially through the stress decoupling conduit.
[0050] Decoupling catheter implantation and tolerance control: After removing the drilled battery, the inner wall of the micro-invasive through-hole and the negative terminal face of the battery body are wiped with anhydrous ethanol to remove oil and residual debris. A micro-nano precision clamp is used to hold the stress decoupling catheter, keeping it vertical and slowly inserting it into the mounting hole. The insertion depth is monitored in real time using a depth gauge to ensure that the bottom end of the catheter is suspended within the central cavity of the core, forming a standard-width annular micro-slit between the stress decoupling catheter and the mounting hole to meet capillary permeation conditions. After implantation, the catheter is left to stand to ensure that it is coaxial with the through-hole without deviation.
[0051] Sensor Suspension Calibration: The polyimide-coated FBG fiber optic sensor is inserted into the stress decoupling conduit through the central cavity from the top of the conduit, ensuring a pre-defined gap between the outer surface of the fiber optic sensor and the inner wall of the stress decoupling conduit. A miniature displacement stage is used to hold the fiber pigtail, and the fiber is slowly pushed forward. The FBG sensing grid area is precisely positioned at the center of the core's axial heat core according to the battery specifications. After assembly, the fiber condition is checked to ensure that a free gap is maintained between the outer wall of the fiber and the inner wall of the conduit throughout the process, and that the fiber remains suspended without compression or adhesion to the wall.
[0052] Primary micro-slit capillary permeation process: Using an ultra-fine needle micro-dispensing valve, low-viscosity anaerobic adhesive is drawn up and placed at the junction of the conduit and the battery casing, precisely dispensing 0.04mL-0.06mL of anaerobic adhesive. Relying on gravity and the capillary suction of the annular micro-slits, the adhesive autonomously permeates downwards along the slits, with the permeation time controlled at 10-15 minutes to ensure that the entire slit is filled with adhesive. The glove box adhesive dispensing equipment is closed. Under the anaerobic environment and the ion catalysis of the metal pore walls, the anaerobic adhesive begins to cross-link. After standing at room temperature for 22-26 hours, it is completely cured, forming a dense primary permeation airtight layer, thus establishing a primary permeation sealing structure.
[0053] Secondary UV spot molding process: UV-curable resin is uniformly coated on the outer through-hole port of the battery and the exposed section of the conduit. Utilizing the surface tension of the resin, a hemispherical adhesive layer is naturally formed, encapsulating the exposed section of the conduit and the fiber optic lead-out root. A 365nm wavelength UV LED light source is used, vertically irradiated with a light intensity of 1800mW / cm²-2200mW / cm² for 50-70 seconds, causing rapid resin curing and forming a hemispherical, encapsulated secondary reinforcement structure. After curing, the overall encapsulation process is complete.
[0054] This invention utilizes a synergistic effect of graded sealing to achieve ultra-high airtightness: the first stage employs anaerobic adhesive that spontaneously permeates and cures anaerobically within the annular micro-slit, forming a dense sealing layer that covers the entire depth of the mounting hole, completely filling even micro-slits only tens of micrometers wide; the second stage uses photocurable resin to form a hemispherical coating structure at the external port, sealing any possible residual openings in the micro-slit and providing mechanical reinforcement for the stress decoupling conduit. This dual sealing effect allows the sealant to withstand internal battery pressure fluctuations and thermomechanical fatigue during long-term cycling. By transforming complex adhesive application and positioning into controlled machining tolerances and capillary self-absorption, this encapsulation process completely eliminates the heavy reliance on operator "feel" in traditional laboratory settings, reducing manufacturing obstacles for research institutions and vehicle manufacturers in establishing standardized in-situ battery testing sample libraries.
[0055] This invention uses an 18650 type power battery as an example to illustrate the above packaging process: Battery: 18650 ternary NCM lithium-ion battery (3200mAh). Conduit: High-purity polyetheretherketone (PEEK) tubing, extruded, outer diameter 0.70mm, inner diameter 0.40mm, total length 68mm. PEEK material is not only chemically inert (able to withstand boiling strong acids and electrolytes for extended periods), but also has a Young's modulus as high as 3.6GPa, making it an excellent material for stress isolation. Fiber Optic Sensor: Single-mode FBG fiber, grating region length 3mm, fiber cladding outer diameter 125um, coated with a 15um thick polyimide high-temperature resistant and electrolyte-resistant swelling coating, total outer diameter 155um. Sealing Materials: Primary adhesive uses Loctite 648 high-strength cylindrical anaerobic adhesive; secondary adhesive uses Dymax modified acrylic photocurable resin (Shore hardness D75). The encapsulation process node state evolution diagram is shown below. Figure 6 As shown.
[0056] High-purity inert environment for centering minimally invasive drilling: For absolute safety, a programmable electronic load is used to discharge the 18650 battery at a constant current to a cutoff voltage of 2.5V (SOC 0%). The battery is then moved into a high-specification vacuum glove box, where it is repeatedly evacuated and refilled with high-purity argon gas to ensure an extremely low dew point (water <0.1ppm, oxygen <0.1ppm). This is to prevent the trace amounts of electrolyte remaining at the moment of drilling from undergoing severe oxidation upon contact with oxygen. The battery is inverted with the negative metal base facing upwards and clamped onto a miniature high-precision bench drill. A 0.75mm diameter high-hardness tungsten carbide micro-drill bit is selected. To prevent localized pyrolysis and gas generation of the electrolyte due to frictional heat, water cooling (using fluorinated liquid) is activated or extremely low-speed cutting is adopted: the spindle speed is limited to 600rpm, and the Z-axis stepper motor controls the feed rate at 0.05mm per second. The drill slowly penetrated the approximately 0.6mm thick nickel-plated steel shell and the underlying insulating gasket, reaching a depth of 3.0mm. At this point, the drill bit was lowered into the air, signifying successful penetration into the central cavity of the core. A strong negative pressure vacuum nozzle was continuously activated alongside the drill bit, using airflow and strong magnetism to instantly remove all iron filings, ensuring that any remaining debris fell into the cavity and triggered a micro-short circuit.
[0057] Implantation of the micro-tolerance-fitted PEEK rigid isolation conduit: Wipe the micropores and surrounding oil stains with a lint-free cloth dampened with anhydrous ethanol. Using a precision micro-nano fixture, the PEEK stress decoupling conduit with its end face flushed is vertically and slowly inserted into a 0.75mm diameter mounting hole. The drilled hole diameter (0.75mm) is slightly larger than the outer diameter of the PEEK tube (0.70mm), creating an extremely narrow annular gap of only 25um on one side in physical assembly, which perfectly meets the optimal response threshold for subsequent capillary pull. A vernier depth gauge is used to monitor and ensure that the bottom of the PEEK tube is suspended, maintaining a 2.0mm safety buffer distance from the inner surface of the positive electrode explosion-proof cover of the battery body, preventing the bottom of the tube from puncturing the positive electrode and causing a short circuit when the vehicle vibrates.
[0058] "In-tube zero-gravity" sensor suspension deployment: A PI-coated FBG fiber optic sensor is inserted from top to bottom into the internal cavity of a PEEK conduit. A miniature displacement stage is used to hold the fiber pigtail and precisely push it in until the FBG sensing grid section is 32.5mm below the tube opening. This position is precisely the axial geometric center of a standard 18650 battery, and also the "thermal core extreme point" where thermal resistance is greatest and temperature accumulation is fastest. The 155µm outer diameter fiber has a 122.5µm free gap on one side within a 400µm inner diameter tube. The fiber is completely "suspended" within the tube, without experiencing any physical compression from the tube wall.
[0059] Primary anaerobic capillary deep penetration barrier curing: Please refer to Figure 2 and Figure 4 A microdispensing valve equipped with a 30G (0.16mm inner diameter) ultrafine needle was used. The needle tip was placed against the junction between the PEEK tube and the outer surface of the negative electrode steel shell. Only 0.05mL of Loctite 648 anaerobic adhesive was precisely dispensed. The mixture was allowed to stand for 15 minutes. Under the combined pull of gravity and strong micro-slit capillary suction (Washburn mechanism), the low-viscosity adhesive (400mPa·s) penetrated and filled the extremely deep micro-slits, 25µm wide and 3.0mm deep. After 24 hours at room temperature, a three-dimensional, dense, primary permeable, airtight layer interlocked with the metal lattice was formed. This layer cut off the nanochannels for electrolyte evaporation and leakage.
[0060] Secondary UV spot structure formation: A suitable amount of Dymax UV adhesive is applied to the top end. Utilizing its high surface tension, the adhesive naturally bulges, forming a perfectly hemispherical droplet with a base diameter of 3.5mm and a height of 2.5mm, tightly encasing the protruding PEEK tube tip and the fragile fiber optic lead in the center. A specific 365nm wavelength UV LED point light source is then activated at 2000mW / cm². 2 The UV adhesive is subjected to high-intensity, close-range, vertical irradiation for 60 seconds. The photoinitiator inside the UV adhesive is excited and transforms from a liquid state into a high-modulus structure within seconds, forming the secondary structural reinforcement layer of this invention. This allows the external leads to withstand lateral tension without loosening and resist vehicle vibration.
[0061] In one embodiment, the effectiveness of the present invention is verified through comparative experiments; wherein, control group A (comparative example): using the traditional method, holes are directly drilled and optical fibers are inserted, followed by a large amount of single-component high-strength epoxy resin (to completely bond the optical fiber to the electrode). Experimental group B (the present invention): using a standard-prepared composite decoupling system of "PEEK conduit + internal anaerobic permeation + external UV end cap".
[0062] Test 1: Two sets of batteries were placed in a 25℃ high-precision constant temperature bath, and a continuous deep cycle of 1C constant current charging / discharging was initiated. The wavelength trajectory of the optical fiber was tracked using a demodulator. The comparison curves of the center wavelength drift trajectories of FBG optical fibers with different structures under the same 1C constant current charge / discharge cycle conditions are shown in the figure below. Figure 7 As shown in the figure, experimental group B of the present invention conforms to the extremely smooth parabolic shape of the heat conduction theory, and the thick-walled structure of the duct absorbs deformation stress.
[0063] Test 2: First, the initial leakage rate was measured. Then, the battery was placed in a three-cell thermal shock test chamber and subjected to a thermal shock (-40℃ for 30 minutes, followed by rapid transfer to +85℃ for 30 minutes), simulating the most extreme thermal expansion and contraction tearing damage under extreme cold winter and high-voltage fast charging conditions. After 100 cycles, the leakage rate decay was measured again. The radar chart comparing the high-precision helium mass spectrometry leak rate decay of different packaging systems before and after 100 extreme temperature shocks is shown below. Figure 8 As shown, by Figure 8 It can be seen that the packaging process used in this invention It has an excellent retention rate. It should be noted that although the steps in the flowchart above are shown sequentially as indicated by the arrows, these steps are not necessarily executed in the order indicated by the arrows. Unless otherwise specified in this document, there is no strict order requirement for the execution of these steps, and they can be executed in other orders.
[0064] A third aspect of this invention provides a battery with an integrated fiber optic sensing structure as described in the first aspect, enabling in-situ, high-precision, long-term monitoring of the battery's internal core temperature, suitable for electric vehicles, energy storage power stations, and other applications. The battery also includes other battery components, which will not be detailed here. The battery body is a standard cylindrical lithium-ion battery such as 18650, 21700, or 4680; the negative terminal face of the battery body integrates mounting holes, stress decoupling conduits, a suspended fiber optic sensor, and a graded sealing assembly, enabling real-time, high-precision acquisition of the core temperature inside the cell.
[0065] A fourth aspect of this invention provides an electric vehicle, including the battery as described in the third aspect. Furthermore, the electric vehicle also includes other automotive components, which will not be elaborated upon here; wherein, a fiber optic sensor embedded inside the battery collects temperature signals and transmits them to the vehicle's control system for early warning of battery thermal runaway.
[0066] In summary, this invention relates to the field of lithium-ion battery safety monitoring and sensing packaging technology, and discloses a fiber optic sensing implantation structure and its packaging method, a battery, and an electric vehicle. The structure includes a stress decoupling conduit and a graded sealing assembly. The stress decoupling conduit is inserted into a mounting hole in the center of the battery, with a safe distance between its bottom end and the inner side of the positive electrode explosion-proof cover of the battery body. An annular micro-slit is formed between the outer wall of the conduit and the inner wall of the mounting hole. The fiber optic sensor is suspended in the central cavity of the conduit, with a preset gap between it and the inner wall. The graded sealing assembly includes an anaerobic adhesive that has been permeated and cured in the annular micro-slit, and a light-cured resin that covers the external port of the mounting hole and the surface of the battery casing, and is hemispherically wrapped around the exposed section of the conduit and the outer side of the fiber optic sensor lead-out section. Mechanical isolation is used to achieve temperature-pressure decoupling, obtaining a pure temperature signal. Graded sealing is used to achieve long-term leak prevention, overcoming the problems of cross-sensitivity and easy seal failure in existing in-situ fiber optic sensing.
[0067] The various embodiments in this specification are described in a progressive manner. For directly identical or similar parts of the embodiments, refer to each other. Each embodiment focuses on its differences from other embodiments. In particular, the system embodiments are basically similar to the method embodiments, so the description is relatively simple; relevant parts can be referred to the descriptions in the method embodiments. It should be noted that the technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification.
[0068] The embodiments described above are merely preferred embodiments of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various improvements and substitutions without departing from the technical principles of this invention, and these improvements and substitutions should also be considered within the scope of protection of this application. Therefore, the scope of protection of this patent application should be determined by the scope of the claims.
Claims
1. A fiber optic sensing implantation structure, characterized in that, Includes stress decoupling conduits and graded sealing assemblies; among which, The stress decoupling conduit has an axially penetrating central cavity, allowing the fiber optic sensor to pass through the central cavity and a preset gap to be provided between it and the inner wall of the stress decoupling conduit; the outer diameter of the central cavity is smaller than the diameter of the mounting hole opened at the center of the negative end face of the battery body, so as to form an annular micro-slit between the outer wall of the stress decoupling conduit and the inner wall of the mounting hole; the lower end of the stress decoupling conduit extends into the battery core cavity in a suspended manner, and a safe distance is provided between the bottom end and the inner side of the positive electrode explosion-proof cover plate of the battery body; The graded sealing assembly is disposed at the assembly interface between the mounting hole and the stress decoupling conduit; the graded sealing assembly includes a first sealing layer and a second sealing layer arranged coaxially; wherein, the first sealing layer is formed by capillary penetration and curing of anaerobic adhesive in the annular micro-slit, filling the annular micro-slit; the second sealing layer is formed by curing with photocurable resin, covering the external port of the mounting hole and the surface of the battery casing, and hemispherically wrapping the exposed section of the stress decoupling conduit and the outer side of the lead-out section of the fiber optic sensor.
2. The fiber optic sensing implantation structure according to claim 1, characterized in that, The stress decoupling conduit is made of polyetheretherketone (PEEK) and has a Young's modulus of 3.6 GPa-4.0 GPa.
3. The fiber optic sensing implantation structure according to claim 1, characterized in that, The stress decoupling conduit has a length of 68 mm, an outer diameter of 0.7 mm, and an inner diameter of 0.4 mm.
4. The fiber optic sensing implantation structure according to claim 1, characterized in that, The aperture is 0.02mm-0.05mm larger than the outer diameter; the width of one side of the annular microslit is 25μm.
5. The fiber optic sensing implantation structure according to claim 1, characterized in that, The preset gap is 122μm-125μm; the safety gap is 1.5mm-2.5mm.
6. The fiber optic sensing implantation structure according to claim 1, characterized in that, The anaerobic adhesive is made of methacrylate and has a dynamic viscosity of 200 mPa·s-500 mPa·s.
7. The fiber optic sensing implantation structure according to claim 1, characterized in that, The light-curing resin is made of acrylic ester, and its Shore hardness after curing is not less than D70; the bottom diameter of the hemisphere is 3mm-4mm, and the height of the hemisphere is 2mm-3mm.
8. A method for packaging an optical fiber sensing implanted structure as described in any one of claims 1 to 7, characterized in that, include: Under an inert gas protective environment, a mounting hole is drilled at the central axis of the negative terminal face of the battery body so that the mounting hole penetrates the battery casing and enters the core cavity; the diameter of the mounting hole is larger than the outer diameter of the central cavity that runs through the stress decoupling conduit axially. The stress decoupling conduit is vertically inserted into the mounting hole so that the bottom end of the stress decoupling conduit is suspended in the core cavity, and an annular micro-slit is formed between the stress decoupling conduit and the mounting hole. The fiber optic sensor is inserted into the stress decoupling conduit through the central cavity, so that a preset gap is provided between the outer surface of the fiber optic sensor and the inner wall of the stress decoupling conduit. Anaerobic adhesive is applied to the root of the connection between the mounting hole and the stress decoupling conduit. The anaerobic adhesive is then allowed to penetrate deep into the annular micro-slit using capillary action and naturally cures in an anaerobic environment to form a primary permeation sealing structure. A photocurable resin is coated on the outer side of the external port of the mounting hole and the exposed section of the stress decoupling conduit, and the photocurable resin is cured by irradiation with ultraviolet light of a specific wavelength to form a hemispherical encapsulated secondary reinforcement structure.
9. A battery, characterized in that, Includes the fiber optic sensing implantation structure as described in any one of claims 1 to 7.
10. An electric vehicle, characterized in that, Includes the battery as described in claim 9.
